Endothelial to Mesenchymal Transition: An Insight in Atherosclerosis - Huang, Qingyan; Gan, Yuhong; Yu, Zhikang; Wu, Heming; Zhong, Zhixiong (Frontiers in Cardiovascular Medicine, 2021)
Atherosclerosis is a fundamental disease of the cardiovascular system and cause great morbidity and mortality worldwide. Endothelium is the first protective barrier of atherosclerosis. Endothelial cells have the potential plasticity of transformation into mesenchymal cells, also termed endothelial to mesenchymal transition (EndMT). On the one hand, EndMT contributes to atherosclerosis from endothelial cell disfunction to plaque formation. On the other hand, risk factors induced atherosclerosis could lead to EndMT. Evidence has demonstrated that EndMT existed in the development of atherosclerosis. Therefore, a deeper understanding of the effect and molecular mechanisms of EndMT on atherosclerosis will provide insights for reversing atherosclerosis.